Answer:
Kendal will be 60 meters away from the library after 80 seconds and again after 100 seconds.
Step-by-step explanation:
6s -540 = 60 or 6s - 540 = -60
<u>First equation</u>
addition property of equality: 6s -540 + 540 = 60 + 540
simplify: 6s = 600
division property of equality: 6s/6 = 600/6
simplify: <em>s = 100</em>
<u>Second equation</u>
addition property of equality: 6s -540 + 540 = -60 + 540
simplify: 6s = 480
division property of equality: 6s/6 = 480/6
simplify: <em>s = 80</em>
The correct answer is d) The maximum number of footballs the team can purchase is 44.
this is true because if we plug 44 into the equation it is the only value that is can fit into the equation without it becoming false.
975 + 34(44) ≤ 2500
2471 ≤ 2500
Answer:
We need to do difference so we can have how many numbers differ between the 2 numbers
Step-by-step explanation:
For example: 5-2=? We want to know what is the difference between the number which is 3 hope I explained it the best I can!!
The average rate of change from x = -1 to x = 2 is 2
<u>Solution:</u>
Given function is:
f(x) = 2x - 1
We have to find the average rate of change from x = -1 to x = 2
<em><u>The average rate of change is given as:</u></em>
![\text {Average rate of change}=\frac{f(b)-f(a)}{b-a}](https://tex.z-dn.net/?f=%5Ctext%20%7BAverage%20rate%20of%20change%7D%3D%5Cfrac%7Bf%28b%29-f%28a%29%7D%7Bb-a%7D)
<em><u>The average rate of change from x = -1 to x = 2 is given by formula:</u></em>
![\text {Average rate of change}=\frac{f(2)-f(-1)}{2-(-1)}\\\\\text {Average rate of change}=\frac{f(2)-f(-1)}{3}](https://tex.z-dn.net/?f=%5Ctext%20%7BAverage%20rate%20of%20change%7D%3D%5Cfrac%7Bf%282%29-f%28-1%29%7D%7B2-%28-1%29%7D%5C%5C%5C%5C%5Ctext%20%7BAverage%20rate%20of%20change%7D%3D%5Cfrac%7Bf%282%29-f%28-1%29%7D%7B3%7D)
<em><u>Find f(2) and f( - 1)</u></em>
<em><u>Substitute x = 2 in given function</u></em>
f(2) = 2(2) - 1 = 4 - 1 = 3
<em><u>Substitute x = -1 in given function</u></em>
f( - 1) = 2(-1) - 1 = -2 - 1 = -3
<em><u>Substitute the values in above formula,</u></em>
![\text {Average rate of change}=\frac{3-(-3)}{3}=\frac{6}{3}=2](https://tex.z-dn.net/?f=%5Ctext%20%7BAverage%20rate%20of%20change%7D%3D%5Cfrac%7B3-%28-3%29%7D%7B3%7D%3D%5Cfrac%7B6%7D%7B3%7D%3D2)
Thus average rate of change from x = -1 to x = 2 is 2